Frequency and Pattern of Myths and Misconception regarding Covid- 19 Vaccine in General Population - Saima Jatoi, Manzoor Ali, Sunil Dat Maheshwari, Masood Uz Zaman, Muhammad Adnan Bawany, Hasham Masood Qureshi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency and pattern of myths and misconceptions regarding COVID-19 vaccine in the general population at Isra University Hospital Hyderabad Material and Methods: This cross-sectional survey base study was conducted at the Isra University Hospital Hyderabad, during a period of six months from August 2021 to January 2022. All the patients who visited the OPD and their attendants of any age or gender, were included. All the subjects were properly counseled that their privacy was fully secured and their name and contact numbers were taken. After obtaining sociodemographic information, the participants were interviewed regarding COVID-19 infection in the past, previous vaccination history for diseases other than COVID-19, conceptions, and myths regarding COVID-19 vaccination, acceptance of COVID-19 vaccination, reasons to vaccinate for COVID-19, and reasons not to vaccinate for COVID-19. All the information was gathered via study proforma including questioner and SPSS version 26 was used for the purpose of data analysis. Results: A total of 145 individuals of either gender were studied regarding myths and misconceptions of COVID-19 vaccine, their average age was 27.71+9.86 years and females were in majority 62.1%. Among the study population, doctors, private employee and housewives were the most common as 44.1%, 11%, 11.7% and 9% respectively. Most of the cases 62.1% were unmarried. According to the myths and misconceptions, 8.3% said it can affect fertility, 23.4% had no trust on its effectiveness and safety, 14.5% said it is an artificial infection procedure, 11% were afraid from its dangerous side effects, 3.4% said the vaccine will change their DNA, 13.8% said it is a controversial substance and 6.9% afraid that they will die within 2 years. 24.1% cases heard myths from family, 24.8% heard from friends and 51% heard by social media. 17.2% had idea that it is an international conspiracy and 4.8% said this may cause sexual dysfunction and 4.8% said it is a procedure of implanting microchip to control them. Conclusion: There were several misconceptions in the general population, most myths like effects of male fertility, distrust on vaccine efficacy, they will be infected artificially, fear of dangerous side effects, controversial substances were observed to be the commonest myths and misconceptions regarding the COVID-19 vaccine in the general population. Above ideas were adopted mostly by the friends and social media.